Sustainability of Coffee: An Indigenous Agriculture toward Digital Technology Era - Yopie Brian Suryadhy Panggabean; Hamed Noralla Bakheet Ali (Universitas Hasanuddin, 2023)
This paper deals with sustainability of coffee as indigenous farming toward digital technology. Indigenous agricultural knowledge (IAK) has long been a driving force in agricultural development. IAK is systematic and collective knowledge, practices, and beliefs about the relationship between living beings and their environment that have been passed down from generation to generation through cultural transmission. This study employed a comprehensive literature review to investigate the publisher of publications with identical titles Some of the knowledge that still exists on indigenous agriculture in communities can be a setback to agricultural progress as it has the potential to become several barriers that development strategies have neutralized over the years. Modern technology is having a growing impact on how traditional agriculture is aided. With the help of contemporary technology, farmers can now access a variety of data about what people in the world need and prepare for another challenge in the competition in the same business of agriculture. This is because they have considerable market potential and resources that can contribute to sustainable economic growth. With today's technological advancements, indigenous-based agriculture can keep up with digital technological advances in helping agriculture-dependent communities increase the productivity of arabica coffee and improve farmers' incomes. The role of digital will not eliminate the part of traditional custom-based agriculture. Still, it can maintain and preserve the custom as a cultural heritage while not forgetting the main objectives needed by people who depend on agriculture.